Applications of Short Memory Fractional Differential Equations with Impulses - Shiri, Babak; Wu, Guo-Cheng; Baleanu, Dumitru (Discontinuity, Nonlinearity, and Complexity, 2026)
Dynamical systems' behavior is sometimes varied with some impulse and sudden changes in process. The dynamics of these systems can not be modeled by previous concepts of derivative or fractional derivatives any longer. The short memory concept is a solution and a better choice for fractional modeling of such processes. We apply short memory fractional differential equations for these systems. We propose collocation methods based on piecewise polynomials to approximate solutions of these equations. We provide various examples to demonstrate the application of the short memory derivative for impulse systems and efficiency of the presented numerical methods.